3-Acrylamidopropyl-trimethylammoniumchloride cationic hydrogel modified graphite electrode and its superior sensitivity to hydrogen peroxide. Issue 9 (2nd September 2019) - Caglar, Aykut; Kazıcı, Hilal Çelik; Alpaslan, Duygu; Yılmaz, Yonca; Kivrak, Hilal; Aktas, Nahit
Abstract: A highly sensitive hydrogen peroxide (H2 O2 ) sensor is fabricated by the synthesized 3-Acrylamidopropyl-trimethylammoniumchloride (p(APTMACl)) hydrogel to covered of pen- graphite (PG) electrodes. (p(APTMACl))-PG electrode is characterized using scanning electron microscopy (SEM), Fourier Transform Infrared (FTIR) spectroscopy, and thermogravimetric analysis (TGA). The electrochemical properties of these sensors are investigated by cyclic voltammetry (CV), differential pulse voltammetry (DPV), and electrochemical impedance spectroscopy (EIS). The CV behavior of (p(APTMACl))-PG electrode is investigated in 0.1 M PBS (pH 7, 5 mm diameter of mold). The developed sensor displays significantly enhanced electrocatalytic activity through the H2 O2 detection. Linear response of the sensor to H2 O2 were observed in the concentration range from 0 to 130 µM (R 2 = 0.99) with a detection limit of 1.08 × 10 −6 M, quantification limit of 3.62 × 10 −6 M (S/N = 3) and sensitivity of 2375 µA/mMcm 2 . In addition, interference studies reveal that (p(APTMACl))-PG electrode is not affected by ascorbic acid (AA), uric acid (UA), and dopamine which are common interfering species. The developed sensor is also successfully applied to detect H2 O2 in real commercial samples. This study describes a novel strategy to sensing characteristics to hydrogen peroxide by p(APTMACl)-PG electrode.